Major Issues in Bringing About Sustainability - Mircea Saveanu (CES Working Papers, 2015)
Research on sustainability is now fast approaching half a century of dedicated work. Although there have been significant breakthroughs, sustainability and its corollary, sustainable development, have proven a tough nut to crack. In our paper, we have started from some fundamental questions, which have yet to be answered and analyzed the implications that stem from these questions. Going past the problem of weakly quantifiable concepts in the definition, a very important issue is that of individual and community preferences. Specifically, these are all short to mid-term lived, while some sustainability problems, particularly those relating to the environment require a significantly longer time period. Another implication is that, given our limited resources, sustainable development would require a careful balance between investments among the three pillars of sustainability, and not follow a maximization policy. Lastly, we conclude that basing our sustainability policies on premises of linear evolution is a dangerous undertaking.
Keywords: Q01; Q58; 330; sustainability; preferences; sustainable development; resources